2021
DOI: 10.13057/biodiv/d220713
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of indigenous fungal entomopathogens and aqueous leaf extract of Annona muricata against Polyphagotarsonemus latus infesting Jatropha curcas in Indonesia

Abstract: Abstract. Puspitarini RD, Afandhi A, Fernando I. 2021. Evaluation of indigenous fungal entomopathogens and aqueous leaf extract of Annona muricata against Polyphagotarsonemus latus infesting Jatropha curcas in Indonesia. Biodiversitas 22: 2648-2655. The broad mite Polyphagotarsonemus latus (Banks) (Acari: Tarsonemidae) has been known to cause a great deal of injury on Jatropha curcas (L.) plantation in Indonesia. Isolation of indigenous fungal entomopathogens from rhizosphere soils, followed by pathogenicity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Conidia density and viability correlated with the virulence of EPF (Afandhi et al, 2022;Faria et al, 2015). The higher the conidia density, the higher the mortality rate of the insects tested (Puspitarini et al, 2021).…”
Section: Conidia Density and Viability Of B Bassiana On The Evaluated...mentioning
confidence: 94%
“…Conidia density and viability correlated with the virulence of EPF (Afandhi et al, 2022;Faria et al, 2015). The higher the conidia density, the higher the mortality rate of the insects tested (Puspitarini et al, 2021).…”
Section: Conidia Density and Viability Of B Bassiana On The Evaluated...mentioning
confidence: 94%
“…There was a large variation in the conidia production and conidial viability among the collected EPF isolates. Xavier-Santos et al (2011) and Puspitarini et al (2021a) suggested that those parameters are determined by the genetic backgrounds of each isolate, hence are strongly species-and strain-specific. A preliminary in vitro assessment on conidia production and conidial viability is carried out to search for effective naturally occurring EPF isolates as biocontrol agents.…”
Section: Discussionmentioning
confidence: 99%
“…After removing surface litter, 500 g soil at 10-15 cm depth was collected using a garden spade from each sampling unit. The garden spade was sterilized with 85% ethanol after being used to hinder any possible cross-contamination of EPF among the sampling sites (Clifton et al 2015;Puspitarini et al 2021a). Soil samples were put in a plastic bag and brought to the laboratory.…”
Section: Study Area and Collection Of Soil Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant extract from A. muricata extract contain acetogenin compound which give strong enough impact on Lepidoptera larvae through contact, respiration, and digestion [25,29]. Acetogenin inhibits the NADPH enzyme in the mitochondria so that the energy in the cell stops then causes death [6,25,37]. High concentrations of A. muricata leaf extract caused the feeding activity of S. litura larvae has to be stop until death [26].…”
Section: Toxicity Of Plant Extracts Against Faw Larvaementioning
confidence: 99%